18FDG-PET for Early Prediction of Complete Response to Lapatinib and Capecitabine in HER2-Positive Metastatic Breast Cancer: A Case Report. Issue 6 (November 2013) - Riccardi, Ferdinando; Mocerino, Carmela; Barbato, Carmela; Vitale, Maria Giuseppa; Carrillo, Giovanna; Trunfio, Martino; Minelli, Salvatore; Cartenì, Giacomo
Targeted therapies against HER2 (trastuzumab, lapatinib) have improved the efficacy of treatment and the outcome of patients with HER2-positive breast cancer. Lapatinib is a tyrosine kinase inhibitor targeting EGFR1 and HER2: it binds the intracellular domain of these receptors and blocks their downstream signaling pathways. In combination with capecitabine, it is the standard of care for patients with trastuzumab-resistant advanced breast cancer. We present the case of a patient exhibiting a complete and prolonged clinical response to second-line treatment with lapatinib and capecitabine after failure of trastuzumab-based therapy. 18 FDG-PET allowed the detection of disease remission several months before computed tomography. Molecular imaging with 18 FDG seems the most powerful way to measure the pharmacodynamic effects of targeted anticancer drugs. This case report confirms that 18 FDG-PET plays a key role not only in detecting metastatic disease but also in evaluating the response to HER2-directed therapy.